Νερό, ενέργεια και διαχείριση υγρών αποβλήτων - Καραγιάννη, Παναγιώτης (Τμήμα Πολιτικών Μηχανικών και Μηχανικών Γεωπληροφορικής, Σχολή Μηχανικής και Τεχνολογίας, Τεχνολογικό Πανεπιστήμιο Κύπρου, 2015)
Water is crucial good not only for people but for other forms of life, too. However, this particular research project aims to present the use of water in life from a different perspective. The water, under conditions, is able to essentially help in energy recovery and therefore in the release of humanity from conventional methods of generating power. The water as energy source can be found in the oceans. The oceans, which cover the biggest part of the planet, are huge energy storages. This energy can be produced through the waves, the tides and the temperature changes of water. The water in lakes and rivers as well can contribute in the production of energy via hydroelectric power. Hydroelectric power is generated through the exploitation of waterfall in terms of producing electric power. Then, follows a detailed approach of the way, with which is accomplished the waste water purification in the plants appropriate for biological treatment. Biological treatment consists of various stages like pre-treatment, primary treatment, secondary treatment, tertiary treatment and finally decontamination. Apart from the result of waste water purification, through biological treatment, is also produced sewage sludge. Sludge is a product of nutritional value, which can contribute in the production of energy. It is used efficiently, under conditions, for agricultural reasons as a fertilizer and at the same time through anaerobic processing it can produce biogas.
Keywords: Ocean energy; Hydropower; Biological waste treatment; Biogas; Sludge; Cyprus; Ωκεάνια ενέργεια; Υδροηλεκτική ενέργεια; Βιολογική επεξεργασία αποβλήτων; Βιοαέριο; Ιλύς; Κύπρος